A model for more efficient interval training on a CompuTrainer - Thibault, G. (2005)
The proposed model of the dynamic links between the components of an interval training session has practical applications on a pedagogical level and in terms of planning sessions and developing training programs in all cycling disciplines in which MAP, aerobic endurance and anaerobic capacity are key performance factors.